Necessity and Proportionality as Conditions of Self-Defence in International and Islamic Law - Rezwana Mohammadi (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2026)
The right of self-defence is one of the exceptions to the prohibition on the use of force under international law. Both international law and Islamic law recognize this right but require that it meet the principles of necessity and proportionality. This article examines these two principles through a comparative legal analysis. It explains how necessity and proportionality are understood and applied in both legal systems by examining the United Nations Charter, customary international law, judicial decisions, and the main sources of Islamic law. The article also discusses the Caroline case and the intervention in Afghanistan to illustrate the practical application of these principles. The study finds that although both legal systems aim to limit the use of force and prevent abuse of the right of self-defence, they differ in their legal foundations and methods of interpretation. A better understanding of these principles can contribute to a more balanced and lawful application of self-defence in international relations.